Fibronectin-binding protein F1 (prtF1) gene is highly distributed in tetracycline-resistant, erythromycin-sensitive streptococcus pyogenes isolates - Simon, Onyema Azi; Kumar, Suresh; Than, Leslie Thian Lung; Osman, Malina; Awang Hamat, Rukman (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: The internalization process of group A streptococci (GAS) into human cells is one of the crucial steps in the pathogenesis of GAS infections, which could also affect their susceptibility responses toward several antibiotics. Currently, data on the distribution of internalization-associated genes and susceptibility patterns are still lacking in Malaysia. This study investigated the distribution of fibronectin-binding protein F1 (prtF1) and streptococcal pyrogenic exotoxin B (speB) genes in GAS isolates with their susceptibility profiles and source of samples. Methods: We used 43 GAS isolates from our previous stock culture and performed antibiotic susceptibility testing by Kirby-Bauer disk diffusion method and interpreted the results according to the established guidelines. We detected virulence (prtF1 and speB) and resistance (ermA, ermB, mefA, tetM and lnuA) genes by PCR method using established primers and protocols. Results: High resistance rates were observed against doxycycline (58.1%) and clindamycin (16.3%). In comparison, 100.0% and 46.5% of GAS isolates carried speB and prtF1 genes, respectively. tetM and lnuA genes were detected in all respective resistant isolates (100% for each). No macrolide resistance genes were detected. Interestingly, prtF1 gene was highly distributed in doxycycline-resistant than doxycycline-sensitive isolates (60.0% versus 27.8%). Conclusions: High resistance rate of GAS toward doxycycline in our study may potentially reflect the uncontrol dissemination of tetM gene among our isolates. The presence of prtF1 gene among this strain would enhance its ability to evade the intracellular action of antibiotics, which may affect the management of GAS diseases. Thus, close monitoring of GAS by molecular methods is required in the future.